Place Identity of Chinese-Thai People in Korat Town - Nopadon Thungsakul; Marisa Hiranteeyakul (Journal of Mekong Societies, 2022)
Place identity, which refers to the relationship between people and places, is derived from the interactions that demonstrate physical and concrete meanings in social dimensions. A place does not only mean the building and its interior space; it also means the way of life of those who have lived there and built profound memories. The purpose of this article is to synthesize perceptions of the relationship between Chinese-Thai people in Korat and the place where they dwell through the concept of place identity. The study was conducted by surveying place identities from the perceptions and meanings of Chinese-Thai in Korat, using in-depth interviews to obtain the viewpoints of those who are attached to places there. The study revealed that the perception of place identity in the collective memories of Chinese-Thai people illustrates their relationships with the places through their experiences and the environment. The relationships involve the activities, functions, symbols, and meanings that reflect Chinese-Thai identity formed from the ways they trade as well as from their beliefs. The places the people are attached to include the following: Thetsaban 1 Market (Municipal Market 1) and Bun Phaisan Shrine. Relationships were also found among other ethnic groups as seen in their participation in the li-ke festival at the city pillar shrine and their way of paying respect to the Thao Suranaree monument. Certain places that still exist in the memories of the Chinese-Thais were demolished and rebuilt with new meanings. These places, however, are still meaningful to the people who recognize they are attached to them and believe in their values.